Analysis of Promotion, Price Perception, Service Quality, Culture, Brand Image on Consumer Purchase Interest of MSMEs Products in South Minahasa Regency - Keintjem, Karenia; Soegoto, Agus S.; Palandeng, Indrie D. (Yayasan Abdurrauf Cendekia Nusantara, 2025)
This study aims to determine whether Promotion, Price Perception, Service Quality, Culture, and Brand Image have an influence on Purchase Intention toward Micro, Small, and Medium Enterprises (MSMEs) products in South Minahasa Regency. The sample used in this research consisted of 97 respondents who had previously purchased MSMEs products. The data collection techniques involved questionnaires as primary data and literature studies as secondary data. The data were analyzed using multiple regression analysis, tested with IBM SPSS Statistics 29 software. The results indicate that the variables Promotion, Price Perception, Service Quality, Culture, and Brand Image simultaneously have a significant effect on Consumer Purchase Intention. This means that purchase intention is influenced not by a single factor but by multiple factors. Furthermore, each independent variable also has a significant partial effect on the dependent variable. This implies that effective promotion, competitive pricing, high-quality service, alignment with local culture, and a strong brand image can enhance consumer purchase intention for MSMEs products.